Human aggression (Part 1) - Jumat, Rahiman (2012)
Like most behaviors, aggression can be examined in terms of its ability to help a species to reproduce and survive. Animals may use aggression to gain and secure territories, as well as other resources including food, water, and mating opportunities. Researchers have theorized that aggression and the capacity for murder are products of our evolutionary past